Gabon Public Expenditure Review : Improving Spending Quality to Foster Inclusive Growth - World Bank Group (World Bank, Washington, DC, 2019)
The analysis presented in this Public Expenditure Review (PER) is designed to support the efforts of the government of Gabon (GOG) to enhance public expenditure efficiency and improve the quality of public goods and services. The report reviews public expenditure data over an 8-year period, examines trends in the composition and efficiency of spending, and assesses whether spending patterns are consistent with Gabon’s development objectives. The report includes in-depth analyses of public investment and the public wage bill, the two largest budget categories. It also reviews the composition and evolution of non-oil revenue which could play a key role in closing the fiscal deficit. Finally, the report reviews education, social protection, and public health expenditures which are crucial for socioeconomic development and poverty reduction.